Evaluadores de este Número - Editorial, Comité (RUNA, archivo para las ciencias del hombre)
Evaluadores Nacionales Elisa Cragnolino, Universidad Nacional de Córdoba Andrés Dimitriu, Universidad Nacional del Comahue Eva Lamborghini, Universidad de Buenos Aires Andrea Mastrangelo, Universidad Nacional de San Martin Paola Carolina Monkevicius, Universidad Nacional de La Plata Brígida Renoldi, Universidad Nacional de Misiones Alejandro Roig, Universidad Nacional de San Martin Esteban Serrani, Universidad Nacional de San Martin Alicia Szmukler, Facultad Latinoamericana de Ciencias sociales (FLACSO) sede Argentina Lia de la Vega, Facultad de Ciencias Sociales, UNLZ / UNLaM Nicolás Viotti, Facultad Latinoamericana de Ciencias sociales (FLACSO) sede Argentina Evaluadores Extranjeros Gabrie Angelotti, Universidad Autónoma de Yucatán, México Juan Antonio Flores Martos, Universidad de Castilla - La Mancha, España Laura Cecilia López, Universidade do Vale do Rio dos Sinos, Brasil Pablo Neder, Centro Nacional de Investigaciones Científicas (CNRS), Francia. Elsie Rockwel, Centro de Inv. y de Estudios Avanzados del Instituto Politécnico Nacional, México Luiz Fernando Rojo, Universidad estadual de Rio de Janeiro, Brasil María Catarina Zanini, Universidade Federal de Santa Maria, Brasil